Preparation and Application in Water Treatment of Magnetic Biochar - Zhao, Qingshuang; Xu, Ting; Song, Xueping; Nie, Shuangxi; Choi, Sun-Eun; Si, Chuanling (Frontiers in Bioengineering and Biotechnology, 2021)
This paper reviews the preparation of magnetic biochar and application in wastewater treatment, as well as briefly discusses the adsorption mechanism of biochar to remove pollutants and the modification methods of biochar. Due to the good physical and chemical properties of biochar, it has been widely used to absorb pollutants from water. The magnetic biochar is commonly prepared by combining biochar with magnetic material. The biochar is endowed with the characteristics of magnetic response, which could effectively solve the problems of difficult recovery and easy loss of adsorbent in water treatment. Magnetic biochar with high carbon content, large specific surface area, magnetic separation and other excellent properties, has become a hot research topic in recent years. The preparation methods and application properties of magnetic biochar are reviewed. The future research directions of magnetic biochar are put forward in order to provide directions for further research and application of magnetic biochar materials.